Analisis Pertumbuhan Penjualan Dan Struktur Aktiva Terhadap Struktur Pendanaan Eksternal - Syafrida Hani; Dilla Ainur Rahmi (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aims to test the correlation between sales growth, assets structure and external funding structure. Result indicates partially,that sales growth did  not have correlate to external funding structure, neither do assets structure.  Simultaneously, sales growth and  assets structure have no correlation to external funding structure.  There were mean that external funding structure is affected by another variable outside this research.